Parenting style differences among parents of children with and without autism: Parenting styles and autism (Dhaka University Journal of Biological Sciences, 2026)
The present study aimed to compare parenting styles among parents of children with autism and parents of children without autism and to examine the relations among three parenting styles. A total of 140 parents (70 mothers and 70 fathers) were selected through purposive sampling. Of these, 70 parents (35 fathers and 35 mothers) had children with autism, while the remaining 70 parents (35 fathers and 35 mothers) had children without autism. Data were collected using translated versions of the Parenting Styles and Dimensions Questionnaire (PSDQ) and obtained data were analyzed through analysis of variance (ANOVA) and Pearson product–moment correlation coefficients. The three parenting styles were assessed like- authoritative, authoritarian, and permissive. The findings indicated that mean score of authoritative parenting is more than rest of the two (authoritarian and permissive) parenting styles and it further revealed that authoritative parenting uses more among the parents with autistic children. Mothers reported higher use of authoritative and authoritarian parenting than fathers, regardless of child status. In addition, parents of children without autism reported higher levels of authoritarian parenting compared to parents of children with autism. No significant differences emerged in permissive parenting with respect to parental gender or child status. Correlational analyses revealed that authoritative parenting was negatively associated with authoritarian as well as permissive styles, whereas authoritarian and permissive styles were positively associated with one another.Dhaka Univ. J. Biol. Sci. 35(1): 129-139, 2026 (January)